2021
DOI: 10.1177/03000605211012379
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen distribution and risk factors for urinary tract infection in infants and young children with retained double-J catheters

Abstract: Objectives To investigate the pathogens and potential risk factors for urinary tract infection (UTI) in patients with retained double-J catheters (DJCs). Methods In total, 107 infants and young children with DJCs were included in this retrospective analysis. Patients were included in the infection group (n = 30) or non-infection group (n = 77), according to UTI presence or absence. The species and characteristics of pathogens were investigated, and the clinical features of the patients were recorded for furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(50 reference statements)
1
1
2
Order By: Relevance
“…Consistent with our study, gender difference was also observed in patients with UTI after retrograde upper urinary lithotripsy [19]. More similarly, Wang et al found that infants and young children with double-J catheter retention exhibited a higher risk of UTI, largely due to Gram-negative bacilli, and male sex was also a risk factor of UTI [20]. In addition to gender difference, younger age was also considered as a risk factor of UTI, consistent with the previous finding [21].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our study, gender difference was also observed in patients with UTI after retrograde upper urinary lithotripsy [19]. More similarly, Wang et al found that infants and young children with double-J catheter retention exhibited a higher risk of UTI, largely due to Gram-negative bacilli, and male sex was also a risk factor of UTI [20]. In addition to gender difference, younger age was also considered as a risk factor of UTI, consistent with the previous finding [21].…”
Section: Discussionsupporting
confidence: 90%
“…We found that the use of an indwelling drainage tube was a protective factor for UTI, which was inconsistent with prior studies ( 9 , 17 , 18 ). Wang et al performed a retrospective study of 107 infants and young children and found that indwelling drainage tube, male, and double-J catheter retention were independent risk factors for UTI ( 9 ).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the use of an indwelling drainage tube was a protective factor for UTI, which was inconsistent with prior studies ( 9 , 17 , 18 ). Wang et al performed a retrospective study of 107 infants and young children and found that indwelling drainage tube, male, and double-J catheter retention were independent risk factors for UTI ( 9 ). A retrospective study conducted by Kitano et al showed that the indwelling drainage tube, hydronephrosis, and renal stones were associated with an increased risk for UTI ( 17 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation